From plant oils to plant foils: Straightforward functionalization and crosslinking of natural plant oils with triazolinediones. (April 2015) - Türünç, Oğuz; Billiet, Stijn; De Bruycker, Kevin; Ouardad, Samira; Winne, Johan; Du Prez, Filip E.
Abstract : Graphical abstract: Highlights: The reactivity of triazolinediones towards natural fatty acid derivatives is characterized and rationalized. Crude plant oils are crosslinked with bifunctional triazolinediones under ambient conditions. Variations in oil, crosslinker and crosslinking density result in a wide range of glass transition temperatures. All reactions can be monitored visually due to the strong visible light absorption of triazolinediones. Abstract: With the aid of triazolinedione (TAD) chemistry, an additive-free, straightforward functionalization and crosslinking strategy for numerous plant oils was developed. In a first step, model studies on the most common natural fatty acids were performed with the aid of monofunctional TAD moieties. These equimolar functionalization reactions were readily monitored by NMR and MS analysis, further facilitated by the disappearance of the characteristic red colour of the TAD molecule. Then, a series of synthesized, bifunctional TAD molecules were used for the chemical crosslinking of crude plant oils, a process that was typically finished within minutes. In this way, a large variety of polymer networks could be obtained, such as plant oil-based foils, showing a wide range of thermal properties, which can be tuned and rationalized by the chemical structure of the different plant oils.